Celebrate with cupcakes : designs and techniques for creating 30 gorgeous cupcakes - Smith, Lindy , 1964- (David & Charles, 2012)
Take your cake decorating skills to the next level with this fantastic collection of fun and stylish cupcakes - ideal for beginner sugarcrafters or cupcake experts alike. Be inspired by 30 creative cupcake designs for every occasion - from weddings to children's parties. Use the expert sugarcrafting tips and techniques, presented in easy-to-follow step by step, to achieve professional looking cakes every time